Selling IT : the science of selling, buying and deal-making - Mukhopadhyay, Sandip; Pingali, Srinivas; Satyam, Amitabh (New York, NY : Routledge, 2022)
"Information Technology (IT) is an essential core of the economy today. Corporations and governments worldwide rely on it to drive their core strategy, and develop and execute business models. Amounting to over 3 trillion US dollars of worldwide spending, the growing significance of the IT industry in the global economy is now well established. Hence, it is crucial to understand the marketplace within which it exists, and this book presents a systematic analysis of the processes, techniques and methods involved in IT sales and marketing. Selling IT: *Integrates a large IT provider's selling process with the enterprise user's IT buying process to highlight the nuances of selling, marketing and developing IT solutions that create value for customers; *Discusses various key concepts such as value-based IT selling, business case for IT acquisition, vendor evaluation and management, account and customer relationship management, customer segmentation, and techniques for customer acquisition and retention; *Analyses the challenges and opportunities involved in selling digital IT and examines the evolution of jobs and careers based on the changed IT landscape; *Includes lesson plans, case studies, and chapter-wise practice questions to support teaching and learning. The book boasts a robust theoretical foundation supported by a clear exposition of concepts and management theories. It will be of benefit to professionals using organization-mandated selling processes. Young executives with a technology background looking for a sales and marketing career in the IT industry can also effectively use this book. It will also be an essential read for scholars and researchers in B2B marketing, IT consulting, Technology sales, and Digital transformation"--
Understanding IT market -- Business value of IT -- IT project management essentials -- Sales and bid management process -- Buying IT -- Client and account management -- Marketing and sales enablement -- Leading with digital -- Selling cloud to enterprises -- Careers in IT -- today and tomorrow.
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Marketing; Information technology -- Vocational guidance; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing; BUSINESS & ECONOMICS / General; SOCIAL SCIENCE / General